Inaccurate Labelling of Melatonin Gummies: A Concerning Trend - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Melatonin gummies have gained popularity as a sleep aid and are widely available over-the-counter.1,2 However, a recent analysis of 25 melatonin gummy products has revealed a concerning trend of inaccurate labelling, raising important questions about product quality, consumer safety, and regulatory oversight.3 This editorial aims to highlight the findings of the analysis and discuss the implications for both manufacturers and consumers.